(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Nebivolol is a pharmaceutical drug used for the treatment of Hypertension. It is characterized with poor solubility which limits its absorption and dissolution rate which delays onset of action. In the present study, fifteen formulations of solid dispersions were prepared with 1:1:1, 1:5:2 and 1:3:1.5 ratios of drug: carrier: surfactant by solvent evaporation method. There was significant improvement in the rate of drug release from all 15 solid dispersions and the formulation (SD14) comprising Nebivolol: Kleptose HPB: SLS in 1:5:2 ratio has shown enhanced solubility about 42 folds and significant improvement in the rate of drug release i.e. From powder X-ray diffraction (p-XRD) and by scanning electron microscopy (SEM) studies it was evident that polymorphic form of Nebivolol has been converted into an amorphous form from crystalline within the solid dispersion formulation. The present study demonstrated that formulation of Nebivolol solid dispersion is a highly effective strategy for enhancing the bioavailability of poorly water soluble drug Nebivolol.